2015
DOI: 10.1007/s13277-015-4338-6
|View full text |Cite
|
Sign up to set email alerts
|

A polysaccharide from pumpkin induces apoptosis of HepG2 cells by activation of mitochondrial pathway

Abstract: Purified white polysaccharide (PPW) is a homogenous polysaccharide isolated from pumpkin, with an average molecular weight of 34 kDa. In this study, we aimed at examining the anti-proliferative activity of PPW against hepatocellular carcinoma (HCC) HepG2 cells and the underlying mechanisms. We found that PPW-induced inhibition of cell proliferation in HepG2 cells was associated with the induction of apoptosis. Exposure of HepG2 cells to PPW (100, 200, and 400 μg/mL) resulted in a loss of mitochondrial membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…15 The western blot results indicated that pre-treatment with AAP-AW, S1, S2 and S3 significantly reversed the downregu- There is abundant evidence suggesting that the Wnt/β-catenin signalling pathway was involved in the pathogenesis of early-stage ANFH by regulating osteoblast differentiation and bone formation. 15 The western blot results indicated that pre-treatment with AAP-AW, S1, S2 and S3 significantly reversed the downregu- There is abundant evidence suggesting that the Wnt/β-catenin signalling pathway was involved in the pathogenesis of early-stage ANFH by regulating osteoblast differentiation and bone formation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…15 The western blot results indicated that pre-treatment with AAP-AW, S1, S2 and S3 significantly reversed the downregu- There is abundant evidence suggesting that the Wnt/β-catenin signalling pathway was involved in the pathogenesis of early-stage ANFH by regulating osteoblast differentiation and bone formation. 15 The western blot results indicated that pre-treatment with AAP-AW, S1, S2 and S3 significantly reversed the downregu- There is abundant evidence suggesting that the Wnt/β-catenin signalling pathway was involved in the pathogenesis of early-stage ANFH by regulating osteoblast differentiation and bone formation.…”
Section: Discussionmentioning
confidence: 96%
“…21,22 Furthermore, the changes in the expression of Runx2, BMP-2, OSX and OCN were also investigated in MC3T3-E1 cells in response to different and so on. 15 The western blot results indicated that pre-treatment with AAP-AW, S1, S2 and S3 significantly reversed the downregu- There is abundant evidence suggesting that the Wnt/β-catenin signalling pathway was involved in the pathogenesis of early-stage ANFH by regulating osteoblast differentiation and bone formation. 15 The downstream genes of the Wnt/β-catenin pathway, such as Bcl-2 and c-myc, are responsible for the cell cycle and cell apoptosis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Polysaccharides from pumpkins 30 , apples 31 , Taxus chinensis var . mairei 32 , and Ampelopsis megalophylla 33 have induced cell proliferation inhibition and apoptosis in tumor cells.…”
Section: Discussionmentioning
confidence: 99%